Comparasion of Microbiome Composition in Acne Vulgaris Using Metagenomic Shotgun and 16s Rrna - Zahra Zahra; Linda Erlina (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Acne vulgaris is a common skin disease in adolescents and young adults. One factor that plays a role in the development of acne vulgaris is changes in the composition of the microbiome in the skin. The microbiome is the community of microorganisms that live on the surface of the skin and plays an important role in maintaining the ecological balance of the skin. Research on microbiome composition in acne vulgaris has been conducted using various analytical methods, including shotgun metagenomics and 16S rRNA. The aim of this study was to compare the microbiome composition in acne vulgaris using shotgun metagenomics and 16S rRNA. This research method is a literature review while data collection techniques are carried out by library studies obtained from 3 databases Pubmed, Google Scholar and Science Direct. The collected data were then analyzed using qualitative analysis. The results showed that some of the most common bacteria in acne vulgaris, such as Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. In recent years, microbiota screening has been developed using NGS techniques using metagenomic whole genome shotgun and 16S rRNA DNA sequencing analysis. NGS techniques have been able to determine the microbiota of facial skin, and differentiate the bacterial abundance of acne-prone and healthy skin.Keywords : 16s rRNA, Acnes Vulgaris, Microbiome, NGS